Frontispiece: Ion Association in Lanthanide Chloride Solutions. Issue 37 (2nd July 2019) - Finney, Aaron R.; Lectez, Sébastien; Freeman, Colin L.; Harding, John H.; Stackhouse, Stephen
Abstract : Simulations reveal how stable coordination species form in lanthanide solutions : A better understanding of the solution chemistry of the lanthanide (Ln) salts in water would have wide ranging implications in many fields, given that despite much effort, even in simple systems, the mechanisms and thermodynamics of Ln III association with small anions remain unclear. In this Full Paper on page 8725 ff., A. R. Finney, S. Stackhouse and co‐workers employ molecular dynamics (MD), using a newly developed force field, to provide new insights into LnCl3 (aq) solutions. The force field accurately reproduces the structure and dynamics of Nd 3+, Gd 3+ and Er 3+ in water when compared with calculations using density functional theory (DFT). These techniques also could be used for the investigation of more complex solution chemistries of cations in water.